2019
DOI: 10.3390/nu11020290
|View full text |Cite
|
Sign up to set email alerts
|

Blueberries Improve Pain, Gait Performance, and Inflammation in Individuals with Symptomatic Knee Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common joint disorder in the world and is the most frequent cause of walking related disability among older adults in the US, which brings a significant economic burden and reduces quality of life. The initiation and development of OA typically involves degeneration or progressive loss of the structure and function of articular cartilage. Inflammation is one of the major drives of the progression of OA. Dietary polyphenols have been studied for their anti-inflammatory properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 59 publications
0
69
0
Order By: Relevance
“…Of the 453 citations retrieved from multiple sources, seven articles (19,21,22,33,(42)(43)(44) met the eligibility criteria ( Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the 453 citations retrieved from multiple sources, seven articles (19,21,22,33,(42)(43)(44) met the eligibility criteria ( Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Four studies evaluated the nutritional interventions with fruits, specifically the effects observed when blueberry [ 8 ], lyophilized strawberry powder [ 46 ], pomegranate juice [ 47 ], and passion fruit peel extract were consumed [ 48 ]. The studies had a total of 151 participants, and three were randomized and double-blind [ 8 , 46 , 48 ]. All studies compared the intervention group with the control or placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…All studies compared the intervention group with the control or placebo group. Studies evaluating blueberry, strawberry, and passion fruit peel extract revealed that a significant reduction in musculoskeletal pain was observed after the consumption of blueberry, strawberry, and passion fruit peel extract [ 8 , 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a reconstituted freeze-dried strawberry beverage (50 g/day) given to obese adults with radiographic evidence of knee OA significantly lowered serum biomarkers of inflammation including (IL)-6, IL-1 β, and cartilage degradation mediators including matrix metalloproteinase (MMP)-3 [37]. Forty g of freeze-dried blueberry powder given daily for four months to adults with symptomatic knee OA significantly decreased (WOMAC, Western Ontario and McMaster Universities Osteoarthritis Index) total score and subgroups, including pain, stiffness, and difficulty to perform daily activities [38]. Pomegranate juice decreases serum levels of matrix metalloproteinase (MMP)-13 and improves antioxidant status (glutathione peroxidase) in patients with knee OA [39].…”
Section: Discussionmentioning
confidence: 99%